Optic nerve sheath diameter measurement using point-of-care ultrasound to assess intracranial pressure of adult patients with traumatic brain injury in resource-limited setting - Melaku Getachew; Mohammednur Abdulahi; Natan Muluberehan; Zeynu Hussen; Amanuel Alemayehu; Tiliksew Abebe; Abdulaziz Hussein; Peter Hutchinson; Angelos Kolias; Mulugeta Semework; Abenezer Tirsit; Tsegazeab Laeke; et al. (Interdisciplinary Neurosurgery, 2023)
Background: Traumatic brain injury is a disease with high mortality with increased intracranial pressure included in the emergency department. Neuroimaging and intracranial pressure monitoring are limited in resource-limited settings. Optic nerve sheath diameter measurement to assess intracranial pressure indirectly using point-of-care ultrasound is appealing in diagnostics and decision-making. Objectives: We plan to evaluate the utility of point-of-care ultrasound on optic nerve sheath diameter role in traumatic brain injury patients. In these patients, optic nerve sheath diameter measurement was performed immediately postoperatively and 24 h later by trained residents. The procedure was repeated if any change in clinical status was observed. Results: A total of 50 patients were enrolled. Twenty-one patients underwent neurosurgical intervention. Three patients died in hospital. Eighteen patients had optic nerve sheath diameters less than 5 mm, 20 patients had optic nerve sheath diameter between 5 mm and 6 mm, and 12 patients had optic nerve sheath diameter > 6 mm. In 2 patients with changes in clinical condition, the repeat optic nerve sheath diameter assessment showed an increase in optic nerve sheath diameter. Conclusion: Despite limitations, trained health care providers can perform optic nerve sheath diameter. Longer training time and quality assurance are needed to appreciate the impact.